Kosovelovi konsi - Jovanovski, Alenka (Primerjalna književnost, 2005)
A reader's response analysis of Kosovel's poems focuses on the break in the communicative efficacy of an aesthetic experience, in as much as this is suggested by the poet's shift away from his "velvety" lyrics in search of a new poetic expression. The paper's starting point is the relationship between the recipient's turning in on him/herself and his or her openness into the extra-aesthetic sphere. The crisis of the Kant-Schiller scheme of aesthetic experience led avant-garde artists to revolutionise their poetic forms in an attempt to counterbalance the recipient's self-indulgent introspection with an opening out into society, into life itself. Through ironisation of the "beautiful soul", Kosovel's "cons" poems prevent the reader from indulging in introspection; rather they force him to adopt aesthetic distance, from where he/she is able to evaluate him/herself as well as the values of society. In some "cons" poems the two poles of the aesthetic experience's communicative efficacy are in balance, but in others this balance is disrupted through too great an aesthetic distance. In these poems, the constitution of meaning is enabled through a pronounced interpretative activity on the part of the recipient, whereby the interpretative effort corresponds to the effort needed to constitute one's own subjectivity. Since the outcome of both is merely subjectivity as interpretation, the recipient once again fails to open out into society to the satisfactory extent. Kosovel saw a way out of such a condition in socialist activity and in integrals, which would lead the recipient to transform his/her critical self-evaluation and an evaluation of his/her society into action, thereby directly incorporating it into society.
Keywords: Kosovel, Srečko, 1904-1926; slovenska poezija; estetsko izkustvo; recepcijska estetika; umetnost; art; literarna estetika; študije